Mimicking the Nitric Oxide‐Releasing and Glycocalyx Functions of Endothelium on Vascular Stent Surfaces - Nan Lyu; Zeyu Du; Hua Qiu; Peng Gao; Qin Yao; Kaiqin Xiong; Qiufen Tu; Xiangyang Li; Binghai Chen; Miao Wang; Guoqing Pan; Nan Huang; et al. (Advanced Science, 2020)
Abstract Endothelium can secrete vasoactive mediators and produce specific extracellular matrix, which contribute jointly to the thromboresistance and regulation of vascular cell behaviors. From a bionic point of view, introducing endothelium‐like functions onto cardiovascular stents represents the most effective means to improve hemocompatibility and reduce late stent restenosis. However, current surface strategies for vascular stents still have limitations, like the lack of multifunctionality, especially the monotony in endothelial‐mimic functions. Herein, a layer‐by‐layer grafting strategy to create endothelium‐like dual‐functional surface on cardiovascular scaffolds is reported. Typically, a nitric oxide (NO, vasoactive mediator)‐generating compound and an endothelial polysaccharide matrix molecule hyaluronan (HA) are sequentially immobilized on allylamine‐plasma‐deposited stents through aqueous amidation. In this case, the stents could be well‐engineered with dual endothelial functions capable of remote and close‐range regulation of the vascular microenvironment. The synergy of NO and endothelial glycocalyx molecules leads to efficient antithrombosis, smooth muscle cell (SMC) inhibition, and perfect endothelial cell (EC)‐compatibility of the stents in vitro. Moreover, the dual‐functional stents show efficient antithrombogenesis ex vivo, rapid endothelialization, and long‐term prevention of restenosis in vivo. Therefore, this study will provide new solutions for not only multicomponent surface functionalization but also the bioengineering of endothelium‐mimic vascular scaffolds with improved clinical outcomes.